Investigating Gender Differences in Mathematics and Science : Results from the 2011 Trends in Mathematics and Science Survey - Reilly, David; Neumann, David L.; Andrews, Glenda (Research in science education (Australasian Science Education Research Association), 2019)
The underrepresentation of women in science, technology, engineering, and mathematics (STEM)-related fields remains a concern for educators and the scientific community. Gender differences in mathematics and science achievement play a role, in conjunction with attitudes and self- efficacy beliefs. We report results from the 2011 Trends in Mathematics and Science Study (TIMSS), a large international assessment of eighth grade students' achievement, attitudes, and beliefs among 45 participating nations (N = 261,738). Small- to medium-sized gender differences were found for most individual nations (from d = -.60 to +.31 in mathematics achievement, and d = -.60 to +.26 for science achievement), although the direction varied and there were no global gender differences overall. Such a pattern cross-culturally is incompatible with the notion of immutable gender differences. Additionally, there were different patterns between OECD and non-OECD nations, with girls scoring higher than boys in mathematics and science achievement across non-OECD nations. An association was found between gender differences in science achievement and national levels of gender equality, providing support for the gender segregation hypothesis. Furthermore, the performance of boys was more variable than that of girls in most nations, consistent with the greater male variability hypothesis. Boys reported more favourable attitudes towards mathematics and science, and girls reported lower self-efficacy beliefs. While the gender gap in STEM achievement may be closing, there are still large sections of the world where differences remain. [Author abstract]